MORPHOMETRY AND LENGTH-WEIGHT RELATIONSHIP OF COILIA DUSSUMIERI, VALENCIENNES, 1848 FROM MUMBAI WATERS - R. Dhanya, V. M.; Jaiswar, A. K.; Palaniswamy, R.; Chakraborty, S. K. (Journal of Indian Fisheries Association, 2015)
Coilia dussumieri Valenciennes, 1848 a component of 'dol' net fisheryforms an important pelagic resource along northwest coast of India. Thepresent communication deals with morphometry and length - weightrelationship of this species along Mumbai coast. Morphometric study showeda positive correlation among the compared characters. The length-weightrelationship for the species from Mumbai coast was found to be W=0.017L2.423Keywords: Morphometry, length-weight relation, Coilia dussumieri